Molecular Survey of Tick-Borne Pathogens Reveals Diversity and Novel Organisms With Veterinary and Public Health Significance in Wildlife From a National Nature Reserve of China - Yang, Jifei; Wang, Xiaojun; Wang, Jinming; Liu, Zhijie; Niu, Qingli; Mukhtar, Muhammad Uzair; Guan, Guiquan; Yin, Hong (Frontiers in Veterinary Science, 2021)
Wildlife is involved in the maintenance and transmission of various tick-borne pathogens. The objective of the present study was to determine the occurrence and diversity of tick-borne pathogens in free-ranging wild animals collected from Tangjiahe National Nature Reserve of China. Blood or liver samples from thirteen wild animals (five takin, three himalayan goral, three reeves' muntjac, one forest musk deer and one wild boar) were collected and screened for piroplasm, Anaplasma spp., Ehrlichia spp. and SFG rickettsiae by PCR based on different gene loci. Three Theileria species, a potential novel Theileria parasite (Theileria sp. T4) and two Anaplasma species were identified in those wildlife. Theileria capreoli was found in himalayan goral, reeves' muntjac and forest musk deer; Theileria luwenshuni, Theileria uilenbergi and a potential novel Theileria parasite (Theileria sp. T4) were identified in takin. Meanwhile, Anaplasma bovis was identified in himalayan goral, takin, reeves' muntjac, forest musk deer and wild boar; Anaplasma phagocytophilum and related strains was found in takin, reeves' muntjac and forest musk deer. All wildlife included in this study was negative for Babesia, A. ovis, A. marginale, Ehrlichia and SFG rickettsiae. Moreover, co-infection involved Theileria spp. and Anaplasma spp. was observed in eight wild animals. This study provided the first evidence of tick-borne pathogens in free-ranging wild animals from the nature reserve, where contact between domestic and wild animals rarely occurs.